Case Report: Epi-endocardial bridges in refractory cavotricuspid isthmus-dependent atrial flutter: technical analysis of epi-endocardial breakthrough - Matteucci, Andrea; Pandozi, Claudio; Russo, Maurizio; Galeazzi, Marco; Lombardi, Enrico; Mariani, Marco Valerio; Lavalle, Carlo; Colivicchi, Furio (Frontiers in Cardiovascular Medicine, 2024)
Background Typical isthmus-dependent atrial flutter (AFL) is traditionally treated through radiofrequency (RF) ablation to create a bidirectional conduction block across the cavo-tricuspid isthmus (CTI) in the right atrium. While this approach is successful in many cases, certain anatomical variations can present challenges, making CTI ablation difficult. Methods We enrolled four patients with typical counter-clockwise AFL who displayed an epicardial bridge at the CTI. Patients underwent high-resolution mapping of the right atrium and CTI ablation. Results Post-mapping identified areas of early focal activation outside the lesion line which suggested the presence of an epi-endocardial bridge with an endocardial breakthrough, confirmed by recording a unipolar rS pattern on electrograms at that site. A stable CTI block was achieved in all patients only after ablation at the site of the epi-endocardial breakthrough. Conclusions The presence of an epicardial bridge at the CTI, allowing conduction to persist despite endocardial ablation, should be considered in challenging cases of CTI-dependent AFL. Understanding this phenomenon and utilizing appropriate mapping and ablation techniques are essential for achieving successful and lasting CTI block.